1996
DOI: 10.1111/j.1460-9568.1996.tb01239.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Components of the SNARE Complex in Relation to Transmitter Release Sites at the Frog Neuromuscular Junction

Abstract: At the frog neuromuscular junction, neurotransmitter release sites are regularly spaced at 1 micron intervals along the nerve terminal, directly facing postsynaptic folds which contain a high density of acetylcholine receptors. Immunostaining and laser confocal scanning microscopy were used to compare the distribution of presynaptic proteins implicated in exocytosis with that of fluorescent alpha-bungarotoxin. Syntaxin, synaptosome-associated 25 kDa protein and calcium channels were located predominantly at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Immunocytochemical staining demonstrated that syntaxin 1 was consistently present in regions of high Ca channel staining. Previous studies have also noted a colocalization of syntaxin with the presynaptic Ca channel but that the distribution of syntaxin extends beyond that of the release sites (Bouvier et al, 1996;Raciborska et al, 1998). Our findings suggest that this syntaxin 1 is in a nonrelease site complex with MUNC18 -1.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Immunocytochemical staining demonstrated that syntaxin 1 was consistently present in regions of high Ca channel staining. Previous studies have also noted a colocalization of syntaxin with the presynaptic Ca channel but that the distribution of syntaxin extends beyond that of the release sites (Bouvier et al, 1996;Raciborska et al, 1998). Our findings suggest that this syntaxin 1 is in a nonrelease site complex with MUNC18 -1.…”
Section: Discussionsupporting
confidence: 58%
“…Considerable evidence supports direct binding of these two proteins in vitro (Saisu et al, 1991;Yoshida et al, 1992;David et al, 1993;Sheng et al, 1994;Schmid et al, 1995;Vance et al, 1999) and their association has been demonstrated previously at the presynaptic terminal (Bouvier et al, 1996;Seagar and Takahashi, 1998). We first used Ab571 to confirm that syntaxin 1 coimmunoprecipitates with the N-type Ca channel in both chick brain and ciliary ganglion lysates (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern indicates localization both in microvesicles docked at plasma membrane active zones and in clusters of microvesicles in the cytoplasm facing each active zone (Boudier et al 1996).…”
Section: Co-localization Of Calcium Channels Syntaxin 1 and Snap-25 mentioning
confidence: 88%
“…The timing of SNARE complex disassembly, and hence of NSF's action relative to the docking and fusion of two membranes has not been definitively established. In different systems, NSF appears to act before membrane docking (6,7), after membrane docking but before fusion (1,8), or even after fusion (9).…”
mentioning
confidence: 99%